2020
DOI: 10.3390/cancers12040826
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Toxicity of Tyrosine Kinase Inhibitors Used in Chronic Myeloid Leukemia: An Analysis of the FDA Adverse Event Reporting System Database (FAERS)

Abstract: Tyrosine kinase inhibitors (TKIs), the treatment of choice for chronic myeloid leukemia (CML), can be associated to cardiovascular (CV) adverse events (AEs). A case/non-case study was performed using AE reports registered in the Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) database to compare the risk of CV event reports related to TKIs indicated in the management of chronic myeloid leukemia (CML). Disproportionality of CV event-related TKIs was computed using the Reporting Odds Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 35 publications
2
91
1
2
Order By: Relevance
“…Largely reversible pulmonary arterial hypertension has been reported as a rare but serious side effect of dasatinib. [80][81][82] In the DASISION study, pulmonary hypertension was reported in 5% of patients treated with dasatinib compared with ,1% of patients treated with imatinib. 70 Evaluation for signs and symptoms of underlying cardiopulmonary disease before initiating and during treatment with dasatinib is recommended.…”
Section: Dasatinibmentioning
confidence: 99%
See 1 more Smart Citation
“…Largely reversible pulmonary arterial hypertension has been reported as a rare but serious side effect of dasatinib. [80][81][82] In the DASISION study, pulmonary hypertension was reported in 5% of patients treated with dasatinib compared with ,1% of patients treated with imatinib. 70 Evaluation for signs and symptoms of underlying cardiopulmonary disease before initiating and during treatment with dasatinib is recommended.…”
Section: Dasatinibmentioning
confidence: 99%
“…Nilotinib labeling contains a black box warning regarding the risk of QT interval prolongation, and sudden cardiac death has been reported in patients receiving nilotinib. 82 QT interval prolongation could be managed with dose reduction. Electrolyte abnormalities should be corrected before the start of treatment with nilotinib and electrolytes should be monitored periodically.…”
Section: Nilotinibmentioning
confidence: 99%
“…Recently, an FDA analysis of the adverse event reporting system database showed that among 64,232 reported cardiovascular events of cancer patients, 2678 of them are CML patients managed with TKIs. The cardiovascular effects of the TKI used to treat CML were analyzed and are summarized in Table 3 [94]. Determined by the odds ratio, nilotinib treatment is associated with cardiac arrhythmias.…”
Section: The Use Of Tkis In CML and Their Association With Cardiovascmentioning
confidence: 99%
“…A "red" background means that the drug use was associated with an adverse cardiovascular effect. These data were extracted and tabulated presently from information in Supplementary Tables S1-S8 presented in Reference [94].…”
Section: The Use Of Tkis In CML and Their Association With Cardiovascmentioning
confidence: 99%
“…Atherothrombotic events included acute coronary syndromes, and cerebrovascular and lower extremity artery disease (LEAD) events. [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%